Intermittent Fasting as a Dietary Strategy for Obesity Management: A Mini Review - Salima Saad,; Sara Elsherif, (AlQalam Journal of Medical and Applied Sciences, 2026)
Obesity is a chronic, multifactorial disease and a major global public health challenge, associated with increased morbidity and mortality from diabetes, cardiovascular disease, cancers, and metabolic syndrome. Traditional continuous calorie restriction (CCR) has long been the standard dietary approach, but its long‑term sustainability is limited by metabolic adaptation and weight regain. Intermittent fasting (IF) has emerged as a promising alternative strategy, shifting the focus from food choice to timing of intake. This narrative mini‑review synthesizes evidence published since 2015 on the efficacy, safety, and mechanisms of IF in obesity management. Common IF regimens include alternate‑day fasting, the 5:2 diet, and time‑restricted eating. Randomized controlled trials and meta‑analyses consistently show that IF produces clinically meaningful weight loss and cardiometabolic improvements comparable to CCR, with modest advantages in certain protocols. Evidence also suggests potential benefits for body composition, lipid metabolism, and insulin sensitivity, though findings remain heterogeneous. IF appears safe for most adults with overweight or obesity, but is not recommended for vulnerable groups such as children, pregnant women, or individuals with eating disorders. Overall, IF represents a flexible, evidence‑based dietary option for obesity management, with long‑term adherence and personalized application being critical determinants of success. Future research should address sustainability, weight regain, and population‑specific outcomes.